Problemas y perspectivas de la investigación psicoeducacional en el Perú - Montes Iturrizaga, Iván (1992)
The author gives a general review about the problems that exist in psychoeducational research in Peru. He discusses sorne problems that are not only associated with educational psychology, but with psychology in general. He focuse on the background of Peruvian psychologist, research programs and the need of educational psychologist to take into account the educational praxis. Future perspectives and possible ways of solving the problem are analyzed.